Developmental surveillance in general practice. Issue 6126 (10th June 1978) - Jenkins, G H; Collins, C; Andren, S
Abstract : During a two-year study of a developmental surveillance programme covering all children under 5 in a large general practice in the south of England, 2157 children were examined, including 382 newborn babies seen at home. Suspected disorders–excluding those found during non-routine consultations–were discovered in 232 children (15% of boys and 11% of girls), of whom 171 (104 boys and 67 girls) were referred to specialist agencies. The number and nature of the disorders show that routine surveillance on the lines proposed by the Court Committee is worth while. Nevertheless, such programmes could not be started on a national scale without increased resources for the specialist services to which more children would need to be referred.